Impact of the MeckFUSE Pilot Project: Recidivism Among the Chronically Homeless. (24th May 2018) - Listwan, Shelley J.; Hartman, Jennifer L.; LaCourse, Ashleigh
Abstract: Homeless individuals involved in the criminal justice system often have needs that translate into a significant human and financial cost to society. As a result, there has been an interest in developing intervention strategies to aid the homeless with the intent to reduce antisocial behavior. One of these strategies, the Frequent User Systems Engagement (FUSE) model, has garnered support nationwide over the last decade; however, few empirical evaluations of its efficacy exist. The current study utilizes a quasi-experimental design to compare outcomes between a sample of FUSE program participants ( n  = 42) with a similar group not receiving services ( n  = 42). Over the course of the 4-year study period, the FUSE group had fewer arrests and remained "arrest free" in the community for a longer of time, even after controlling for associated risk factors. Recommendations for improvement outcomes utilizing this model are provided.